Testicular Teratocarcinoma in a Ferret (Mustela putorius furo). (November 2020) - Fiddes, Kelsey R.; Murray, Jerry; Williams, Bruce H.
Summary: A 7-month-old male domestic ferret ( Mustela putorius furo ) was presented for evaluation of unilateral testicular enlargement. Microscopic examination of the left testicle revealed a neoplasm with differentiation along multiple cell lines (ectoderm, endoderm, mesoderm) including respiratory epithelium, bone and haired skin. A poorly differentiated epithelial component was dispersed throughout the neoplasm with invasion of testicular lymphatics. The animal developed progressive dysuria and was euthanized. At necropsy, metastasis of the poorly differentiated epithelial component was present in the urinary bladder, ureters, prostate gland, pelvic fat, abdominal and thoracic lymph nodes, kidney and lung. This is the first report of a malignant testicular teratoma with widespread metastasis in this species.